Multiple system atrophy in Hokkaido, Japan: a prospective registry study of natural history and symptom assessment scales followed for 5 years. Issue 2 (8th February 2021) - Matsushima, Masaaki; Yabe, Ichiro; Sakushima, Ken; Kanatani, Yasuhiro; Nishimoto, Naoki; Matsuoka, Takeshi; Sawada, Jun; Uesugi, Haruo; Sako, Kazuya; Takei, Asako; Tamakoshi, Akiko; Shimohama, Shun; et al.
Abstract : Objectives: Multiple system atrophy (MSA) is a refractory neurodegenerative disease, but novel treatments are anticipated. An accurate natural history of MSA is important for clinical trials, but is insufficient. This regional registry was launched to complement clinical information on MSA. Setting: Patient recruitment started in November 2014 and is ongoing at the time of submission. The number of participating facilities was 66. Postal surveys were sent to medical facilities and patients with MSA in Hokkaido, Japan. Participants: After obtaining written consent from 196 participants, 184 overview surveys and 115 detailed surveys were conducted. Primary and secondary outcome measures: An overview survey evaluated conformity to diagnostic criteria and a detailed survey implemented an annual assessment based on the Unified Multiple System Atrophy Rating Scale (UMSARS). Results: At the time of registration, 58.2% of patients were diagnosed with cerebellar symptoms predominant type MSA (MSA-C) and 29.9% were diagnosed with parkinsonism predominant type MSA (MSA-P). UMSARS Part Ⅳ score of 4 or 5 accounted for 53.8% of participants. The higher the UMSARS Part Ⅳ score, the higher the proportion of MSA-P. At baseline, levodopa was used by 69 patients (37.5%) and the average levodopa dose was 406.7 mg/day. The frequency of levodopa use increased over time. Eleven cases changed from MSA-C to MSA-P during the study, but the opposite was not observed. Information about survival and causes of death was collected on 54 cases. Half of deaths were respiratory-related. Sudden death was recorded even in the group with UMSARS Part Ⅳ score of 1. Conclusions: This study is the first large-scale prospective MSA cohort study in Asia. MSA-C was dominant, but the use of antiparkinsonian drugs increased over the study period. Changes from MSA-C to MSA-P occurred, but not vice versa.